2014
DOI: 10.1093/bja/aet408
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary exercise variables are associated with postoperative morbidity after major colonic surgery: a prospective blinded observational study

Abstract: CPET variables are associated with postoperative morbidity. A multivariable model with VO₂ at θ(L) and gender discriminates those with complications after colonic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
120
3
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(131 citation statements)
references
References 41 publications
6
120
3
2
Order By: Relevance
“…36,37 In fact, the American College of Chest Physicians clinical practice guidelines for evaluation procedures of patients with lung cancer being considered for surgical resection recommend the use of CPX to assess risk. 38 The 2014 American College of Cardiology/AHA guidelines on the perioperative cardiovascular evaluation and management of patients undergoing noncardiac surgery also give CPX a Class IIb (Level of Evidence B) rating.…”
Section: Cpx To Assess Perisurgical and Postsurgical Risk And Long-tementioning
confidence: 99%
“…36,37 In fact, the American College of Chest Physicians clinical practice guidelines for evaluation procedures of patients with lung cancer being considered for surgical resection recommend the use of CPX to assess risk. 38 The 2014 American College of Cardiology/AHA guidelines on the perioperative cardiovascular evaluation and management of patients undergoing noncardiac surgery also give CPX a Class IIb (Level of Evidence B) rating.…”
Section: Cpx To Assess Perisurgical and Postsurgical Risk And Long-tementioning
confidence: 99%
“…The time pressure experienced in the UK and internationally may well contribute to the lack of quality research and subsequent evidence base supporting the use of exercise treatments in the period between decision to treat and surgery for colorectal cancer. Given however, that recent work has shown that those with improved cardio-respiratory fitness have lower rates of mortality and complications following colorectal cancer surgery [8,9], this time period provides an opportunity to attempt to improve cardio-respiratory fitness before surgery, with the possibility of reducing peri-operative risk and improving post-operative outcome.…”
Section: Introductionmentioning
confidence: 99%
“…19,39 In practical terms, this degree of variability is potentially significant when considering outcomes in perioperative assessments. 5,11,13,15,22,[39][40][41] In two recent reviews, Levett et al 5,12 summarized studies assessing the association between preoperative VT and postoperative outcomes. These studies among different surgery candidates (including major intra-abdominal, colon, rectal, hepatobiliary, hepatic resection, liver transplant, upper gastrointestinal, bariatric, cystectomy, and AAA repair procedures) showed that values below 9-12 mLO 2 Ákg -1…”
Section: Discussionmentioning
confidence: 99%
“…5,6,[8][9][10][11][12] Ventilatory threshold values were associated with morbidity, mortality, surgery complications, and length of hospital stay. 5,[12][13][14][15][16][17] The VT is defined as an exercise intensity beyond which the increase in ventilation becomes disproportionate to the increase in power output or oxygen uptake during progressive exercise. 11,18 This measure provides important information regarding the major physiological systems involved in aerobic exercise and constitutes a determinant of an individual's functional capabilities and cardiorespiratory performance.…”
Section: Résumémentioning
confidence: 99%
See 1 more Smart Citation